Introduction to WebRTC : fundamentals of real time communication on the Web through simple API's - Sime, Arin (Infinite Skills, 2015)
"In this Introduction to WebRTC training course, expert author Arin Sime teaches you the basic concepts of WebRTC development. This course is designed for users that already have a basic understanding of JavaScript and HTML. Once you have completed this computer based training course, you will be familiar with the basic concepts of WebRTC development and be able to apply them to add voice, audio, and data channels into web applications. Working files are included, allowing you to follow along with the author throughout the lessons."--Resource description page.